Strengthening University Students’ Knowledge Through English Language Teaching in The Era of Society 5.0 - Al-Manduriy, Shahibul Muttaqien; Sayyi, Ach; Pratama, Angga; Muttaqiin, Miftahul (International Conference on Islamic Studies, 2022)
University students are the agents of change in today word Studying English is very important today to expand the possibility to learn more knowledge in today world, since our world have so many varieties of language and English is the most used Language in the world. Society 5.0 is a concept that defines that technology and humans will coexist in order to improve the quality of human life in a sustainable manner. English is become the most used language in the world of technology. Improving the university students’ knowledge about English is to overcome and provide the skill to confront this era of advance technology.